Analysis Of Brand Experience And Brand Satisfaction With Brand Loyalty Through Brand Trust As A Variable Mediation - Megasari Gusandra Saragih; Elfitra Desy Surya; Sri Rahayu; Harianto Harianto; Ramadhan Harahap; Slamet Widodo (Journal of International Conference Proceedings (JICP), 2019)
This research examines the influence of brand experience and brand satisfaction of brand loyalty with brand trust as intervening variable. The samples used in this study were 130 respondents who were Honda motorcycle customers in Medan city. Nonprobability sampling Technique by purposive sampling method is used as a sampling technique. The analysis method is Structural Equation Modeling (SEM) using the AMOS-20 (Analysis of Moment Structure) device. It was found that brand experience and brand Trust have significant effect on brand trust and brand loyalty. Brand Trust is a significant effect on brand loyalty. Brand Trust is a partial mediation the influence of brand experience and brand trust of brand loyalty.